Até os confins da terra: a missão Batista no Pará, missão, linguagem e identidade religiosa na Amazônia Paraense (1968-1978) - Santos, Catarina Maria Costa dos (2014)
This thesis has a general aim to describe the study of mission, language and religious identity in the Amazon region of Pará, with special interest on the Baptist Mission in Pará during the military dictatorship (1968-1978). I present the analysis about the mission with an emphasis on the use of metaphors as a particular system of language that expresses the identity of the group and the Baptist Mission as a collective project that is realized through the individual from local churches articulated to national institutions. The language expresses the missionary identity, which is the link between local and global projects and is the one that produces the feeling of belonging and group cohesion, linking the center to the margins and vice versa through the communication network produced by the Institution. The biblical metaphors are not a simple feature of Baptists missionary rhetoric, they are actually, a well-articulated system of meaning production, that keeps the concepts of the mission, anchored in Bible texts selected from the perspective of Baptist hermeneutic. In this sense, they are necessary because the message update of sowing in contexts such as the Amazon region of Pará during the military dictatorship, being effective to reproduce the precepts of the missionary world and renew the mission central concepts